New insights into the phylogeny of Tortopus Needham and Murphy and Tortopsis Molineri (Ephemeroptera, Polymitarcyidae) with description of three new species - Molineri, Carlos (2021)
The family Polymitarcyidae, with a worldwide distribution, includes mayflies with large burrowing nymphs. South America harbors the highest diversity of this family, including the subfamilies Asthenopodinae and Campsurinae. In this work, three new species belonging to the genera Tortopsis and Tortopus (Campsurinae) are described based on adults and nymphs from Colombia: Tortopsis toro sp. nov., Tortopsis andaki sp. nov. and Tortopus coreguaje sp. nov. Additionally, Tortopsis limoncocha is firstly recorded from Colombia. A cladistic analysis of all the species in these genera is presented, using external morphological characters of adults and eggs. Keys to male and female adults of all the species of both genera are presented.